Shekh Ma Shieraki Anni: Typology of a fictional language created for artistic purposes - Destruel, Matt (Lingua Frankly, 2014)
The goal of this paper is to establish a descriptive survey of Dothraki, using typological data as the main source of information, and then applying linguistic tools to determine if the language is typologically tractable. In order to do so, I selected Greenberg’s (1963) work on linguistic universals, based on its relevance and prevalence even to this day, despite the many other contributions that have been made in the field of typology. Each universal will therefore be applied to the Dothraki language, in order to see if it indeed conforms to most – if not all – of them.